(untitled) (Південний архів (історичні науки), 2025)
The purpose of the study is to analyze the peculiarities of the embodiment and implementation of the ideas of the Catholic Action in the Stanislaviv diocese, to find out how the initiatives of Bishop H. Khomyshyn were in line with the universal principles of secular apostolate, based on documents, in particular, papal encyclicals, pastoral letters, and works by Hryhoriy Khomyshyn. Methodological basis. The study uses historical-comparative and historical-chronological methods, analysis and synthesis, synchronic and diachronic analysis, and the principles of objectivity and impartiality.Results of the study. In the first half of the twentieth century, Catholic Action became the leading form of lay apostolate in the Catholic Church. For the Greek Catholic Church in the Ukrainian lands, this movement was of particular importance due to the challenges of modernization, secularization, and the influence of ideologies. Bishop H. Khomyshyn (1867–1945) played a special role in the implementation of the Catholic Action in the Stanislaviv Eparchy, whose activities went beyond the local and became universal. The study found that the Catholic Action in the Stanislaviv diocese had a clear goal and was based on the ideas of Popes Pius X and Pius XI. A special role in its implementation was played by the institutions created on the initiative of Bishop H. Khomyshyn, in particular, the cultural and educational regional centers of the «Skala» Society. H. Khomyshyn, unlike Metropolitan A. Sheptytsky, emphasized Romanism and strict church discipline, which brought his vision of the problem closer to the Western European model.Conclusions. The Catholic Action in the Stanislaviv Eparchy was an example of a harmonious combination of the universal idea with local church traditions and the historical context of the interwar period. Its implementation contributed to spiritual renewal, the formation of an active laity, and laid the groundwork for a future understanding of the role of believers in the Church. H. Khomyshyn’s experience deserves a deeper understanding in modern religious studies and historical and theological discourse.